Catchment Modelling Of Non – Point Source Pollution Accretion For Rivers - O. E. Ekenta (European Scientific Journal, ESJ, 2016)
Catchment process simulation models are designed to model the interaction of hydrological, geochemical and ecological processes and the effects of change. TOMCAT, a catchment scale model was applied in modeling the transport of determinands from non-point (diffuse) sources to Mimram river, a tributary of the river Thames. The magnitude and timing of the processes taking place is stochastic with the model representing as accurately as possible the systematic and random variability of various model inputs and their inter-relationships. The results indicate that the BOD, NH4N and Un-ionised NH3 loads which enter the rivers from non-point sources increased by 0.55mg/l, 0.024mg/l and 0.001mg/l respectively. These values are relatively small. The Dissolved Oxygen concentration along the reach increased by 2.5 mg/l indicating substantial re-aeration along the reach. The accretion value for the conservative determinand Chloride was 3.75mg/l. Non-point source pollutants accretion to the Mimram is influenced by agricultural and silvicultural practices in the catchment. The results of the investigation indicate that the model could be adopted by environmental pollution control agencies as a management tool for intervention in the area of pollution abatement for catchments.